Harnessing renewable energy in electric power systems theory, practice, policy - Moselle, Boaz; Padilla, Jorge 1983-; Schmalensee, Richard (Earthscan, 2010)
"Drawing on both economic theory and the experiences of the United States and EU member states, Harnessing Renewable Energy addresses the key questions surrounding renewable energy policies. How appropriate is the focus on renewable power as a primary tool for reducing greenhouse gas emissions? If renewable energy is given specific support, what form should that support take? What are the implications for power markets if renewable generation is widely adopted? Thorough and well-evidenced, this book will be of interest to a broad range of policymakers, the electric power industry, and economists who study energy and environmental issues"--Provided by publisher.